2007
DOI: 10.1186/1471-2156-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic affinities between endogamous and inbreeding populations of Uttar Pradesh

Abstract: BackgroundIndia has experienced several waves of migration since the Middle Paleolithic. It is believed that the initial demic movement into India was from Africa along the southern coastal route, approximately 60,000–85,000 years before present (ybp). It has also been reported that there were two other major colonization which included eastward diffusion of Neolithic farmers (Elamo Dravidians) from Middle East sometime between 10,000 and 7,000 ybp and a southern dispersal of Indo Europeans from Central Asia 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…In a large population-based study on 1800 subjects from North India, the genetic studies revealed that upper caste Hindus and Muslims are closer to Whites whereas middle caste are closer to Asians. 41 Solberg and McGarry 42 have reported that atherosclerotic lesion appears in IC arteries about one decade later in life than they do in EC carotid artery; however, in our study this phenomenon has not been observed. The time of flight MRA in the current study was done on a 1.5-T scanner, which has a lower sensitivity and specificity in detecting IC small vessel abnormality compared with digital subtraction angiography.…”
Section: Discussioncontrasting
confidence: 77%
“…In a large population-based study on 1800 subjects from North India, the genetic studies revealed that upper caste Hindus and Muslims are closer to Whites whereas middle caste are closer to Asians. 41 Solberg and McGarry 42 have reported that atherosclerotic lesion appears in IC arteries about one decade later in life than they do in EC carotid artery; however, in our study this phenomenon has not been observed. The time of flight MRA in the current study was done on a 1.5-T scanner, which has a lower sensitivity and specificity in detecting IC small vessel abnormality compared with digital subtraction angiography.…”
Section: Discussioncontrasting
confidence: 77%
“…6 As any other Muslims in the world, Indian Muslims also follow two sects, Shia and Sunni, practicing strict endogamy. [12][13] Consistent with the above historical and anthropological facts, classical markers data [11][12]14 coupled with molecular marker studies [15][16][17][18] suggested the subsistence of high level of regional genetic affinity in some of the north and south Indian Muslim populations. In contrast, a couple of classical marker studies have shown that some of the northern and north western Muslim populations genetically vary from the aboriginal Indian Hindu populations.…”
Section: Contemporary Ethnicmentioning
confidence: 65%
“…Coupling of Indian Shia and Indian Sunni close to Kanyakubj Brahmins was in congruent with previous reports based on mtDNA 17 and the separate set of microsatellite data analyses. 16 The array of populations in the worldwide NJ tree ( Figure 3) and three-dimensional PCA plot (Figure 2b) exemplified Dawoodi Bohras (TN and GUJ) in an intermediary genetic position, especially relative to the Middle Eastern and European population clusters. As expected, Table S5).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown (Saha et al, 2005) that Indian populations exhibit a high degree of genetic admixture and a greater genetic proximity with other world populations. Studies have indicated that the south Indian population is genetically closer to Asian populations (Bamshad et al, 2001), whereas the north Indian population is closer to Caucasian populations (Khan et al, 2007). When a study contains a mixed population, it should be divided into the different ethnicities if data are available.…”
mentioning
confidence: 97%